Preparation of Surfactant-Free Nano Oil Particles in Water Using Ultrasonic System and the Mechanism of Emulsion Stability - Seon-Ae Hwangbo; Seung-Yul Lee; Bu-An Kim; Chang-Kwon Moon (Nanomaterials, 2022)
Emulsion technology is widely used in the preparation of cosmetics, pharmaceuticals, drug delivery, and other daily necessities, and surfactants are frequently used to prepare these emulsions because of the lack of reliable surfactant-free emulsification techniques. This is disadvantageous because some surfactants pose health hazards, cause environmental pollution, have costly components, and place limitations on process development. In this paper, an efficient method for surfactant-free nano-emulsification is presented. In addition, we discuss the effects of different operating parameters on the oil particle size, as well as the effect of the particle size on the emulsion stability. Specifically, we compared three surfactant-free ultrasonic emulsification technologies (horn, bath, and focused ultrasonic systems). The focused ultrasonic system, which concentrates sound energy at the center of the dispersion system, showed the best performance, producing emulsions with a particle size distribution of 60–400 nm at 400 kHz. In addition, phase separation did not occur despite the lack of surfactants and thickeners, and the emulsion remained stable for seven days. It is expected to be widely used in eco-friendly emulsification processes.